Racing the Storm: Racial Implications and Lessons Learned from Hurricane Katrina - Potter, Hillary (Lexington Books, 2007)
On August 29, 2005, Hurricane Katrina hit land and gravely affected the lives of many people in the states along the Gulf Coast. Katrina went beyond demonstrating the devastating natural effects of a hurricane by exposing the continuing significance of race relations and racial stereotyping in U.S. society.Racing the Storm serves to highlight the race-based perceptions of and responses to Katrina survivors by governmental entities, volunteers, the media, and the general public. Scholars from a variety of disciplines take on the task of analyzing the social phenomena and racial implications surrounding Hurricane Katrina.